Evaluation of the degree of aesthetic satisfaction after subcutaneous gluteal fat grafting - Alysson Rogério Matioski; Eduardo Pianaro Caron; Gabriel Paiva Kroneis (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Body exposure, especially in the gluteal region, has increased the demand for gluteoplasty surgery. Autologous adipose tissue has been used to correct soft tissue defects since the beginning of the last century. Its smooth, natural texture, availability in sufficient quantities, and potentially permanent integration make adipose tissue the ideal physiological filler material. In this context, gluteal fat grafting, when compared with the use of gluteal implants, offers a faster recovery period and fewer complications in the medium and long term. Method: A prospective study was conducted using the gluteal evaluation questionnaire in patients who underwent subcutaneous gluteal fat grafting from August to December 2019. The collected data were submitted for statistical analysis by Student’s t-test. Results: Forty patients (39 females and 1 male) who underwent subcutaneous gluteal fat grafting were selected. The average age presented in the study was 36.55 years. The mean body mass index was 27.38 kg/m². The most frequent comorbidities were varicose veins, anemia, and hypertension. In most of the hypotheses evaluated, there was a significant improvement in the quality of life of the selected patients. Conclusions: Subcutaneous gluteal fat grafting improves patients’ quality of life, which is demonstrated by the high level of satisfaction after performing this procedure.